PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG PERKALIAN DAN PEMBAGIAN PECAHAN PADA SISWA KELAS V SDN 1 TAMANWINANGUN TAHUN AJARAN 2016/2017 - Khotimah, Khusnul; Suhartono, Suhartono; Salimi, Moh (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Problem-Based Learning (PBL) in Improving Learning Outcome of Mathematics about Multiplication and Division of Fraction for Fifth Grade Students of SDN I Tamanwinangun in The Academic Year of 2016/2017. The objectives of this research are to improve learning outcome of mathematics about multiplication and division of fraction through the use of PBL model. Subjects of the research were 26 students from fifth grade. Sources of data are teacher and students. This research is conducted within two cycles and four meetings. Each cycle consisted of four stages namely planning, action, observation, and reflection. Techniques of collecting data were observation, interview, and test. The results of this research show that the use of PBL model can improve learning outcome of mathematics about multiplication and division for fifth-grade students.Keywords: Problem Based Learning, multiplication, Division, Mathematics